Market as place and space of economic exchange : perspectives from archaeology and anthropology - Hahn, Hans Peter; Schmitz, Geraldine (Oxbow Books, 2018)
In the context of commodification, material culture has particular properties hitherto considered irrelevant or neglected. First, the market is a spatial structure, assigning special properties to the things offered: the goods and commodities. Secondly, the market defines a principle of dealing with things, including them in some contexts, excluding them from others. The contributions to Market as Place and Space address a variety of aspects of markets within the framework of archaeological and anthropological case studies and with a special focus on the indicators of practices attached to the commodities and their valuation.--